2014
DOI: 10.7763/ijimt.2014.v5.523
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Website Quality and Perceived Trust on Customer Purchase Intention in the Hotel Sector: Website Brand and Perceived Value as Moderators

Abstract: This study investigates the relationships among website quality, website brand, perceived trust, perceived value, and purchase intention in the hotel industry. The study sample was a target chain hotel in Taiwan (i.e., Sheraton). A statistical analysis of the collected questionnaires was computed from a web-based survey. Using the structural equation modeling (SEM) technique, the results reveal that perceived trust is positively influenced by website quality, and purchase intention is positively influenced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 26 publications
6
55
0
9
Order By: Relevance
“…Brand orientation has significant association with customer online purchase intention (Ling et al 2010). Hence, it is mandatory to reform and improve ebranding strategies to attract more online consumers (Chang et al 2014). Trust and brand has tight association between them.…”
Section: Reputationmentioning
confidence: 99%
“…Brand orientation has significant association with customer online purchase intention (Ling et al 2010). Hence, it is mandatory to reform and improve ebranding strategies to attract more online consumers (Chang et al 2014). Trust and brand has tight association between them.…”
Section: Reputationmentioning
confidence: 99%
“…Pre-purchase services consist of product pricing, support of product search evaluation and web appearance [4]. According to previous study, product pricing and website appearance have been found to influence customer intention to purchase over the internet [5]- [9]. Transaction-related services consist of the billing and paying mechanism, delivery arrangement, security and privacy [4].…”
Section: The Antecedents Of Online Purchase In E-commercementioning
confidence: 99%
“…Reliability is related to a perception that a brand can meet consumer's needs; while intention is based on the consumers believe whether the brand will always fulfill their interest when there is an unintentional problems that occurs during consuming the product. The relationship between perceived value and consumer trust has been proved by some empirical research in diverse contexts like green marketing [1][2][3], online services [4,5], umroh and hajj travel service [31], and automobile product [32]. Thus, based on the reveiew of literature above, these are the proposed hypotheses: H1: Hedonic Value significantly and positively influences consumer trust H2: Price Value significantly and positively influences consumer trust H3: Functional Value significantly and positively influences consumer trust H4: Social Value significantly and positively influences consumer trust…”
Section: Consumer Trustmentioning
confidence: 99%
“…One of the factors that drive consumer trust is through improving perceived value of a product. To conduct this research, the author proposes several review of literature that influences consumer trust [1][2][3][4][5]. Yet, it needs to be further explored in the context of herbal medicine whether consumer perception on product value of herbal medicine will influence consumer trust in consuming the herbal medicine product.…”
Section: Introductionmentioning
confidence: 99%